SPIRITUAL ALIENATION OF YOUTH IN UZBEKISTAN: ESSENCE, CAUSES AND FORMS - Khujamov Zokhidjon; Abdurashid ugli (Sciental Journals Publishing, 2025)
This article analyzes the essence, main causes, and forms of spiritual alienation observed among youth in Uzbekistan. Factors such as globalization, the rapid development of information technologies, the influence of culturally inappropriate content, and the weakening of family and social control are identified as key reasons behind the youth’s detachment from national values, historical memory, and social responsibility. The article also examines the manifestations of spiritual alienation, including passivity, individualism, lack of cultural awareness, and susceptibility to radical ideologies. Additionally, the paper provides suggestions and recommendations aimed at developing spiritual immunity among the younger generation.
Keywords: Spiritual alienation, youth, globalization, value crisis, social influence, spiritual education, social security, national idea.